2020
DOI: 10.1631/jzus.a1900383
|View full text |Cite
|
Sign up to set email alerts
|

Performance of rotating detonation engine with stratified injection

Abstract: In this study, a numerical study based on Euler equations and coupled with detail chemistry model is used to improve the propulsion performance and stability of the rotating detonation engine. The proposed fuel injection called stratified injection functions by suppressing the isobaric combustion process occurring on the contact surface between fuel and detonation products, and thus the proportion of fuel consumed by detonation wave increases from 67% to 95%, leading to more self-pressure gain and lower entrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…They indicated that the boundary layer has a negligible effect on the detonation wave velocity and that the pressure in the boundary layer is nearly constant. Therefore, in numerical studies focused on detonation-based engines, viscosity, mass diffusion, and thermal conduction can be neglected, and the twodimensional governing equations are reactive Euler equations [30][31][32][33][34][35]. The Euler equations with source terms in Cartesian coordinates are expressed in Equation ( 1) [36].…”
Section: Methodsmentioning
confidence: 99%
“…They indicated that the boundary layer has a negligible effect on the detonation wave velocity and that the pressure in the boundary layer is nearly constant. Therefore, in numerical studies focused on detonation-based engines, viscosity, mass diffusion, and thermal conduction can be neglected, and the twodimensional governing equations are reactive Euler equations [30][31][32][33][34][35]. The Euler equations with source terms in Cartesian coordinates are expressed in Equation ( 1) [36].…”
Section: Methodsmentioning
confidence: 99%
“…They also proposed a fuel injection scheme, namely stratified injection, to improve the propulsion performance and stability of the rotating detonation engine. This enables a greater gain in self-pressure and a reduction in the generation of entropy (Lei et al, 2020b). With these enhancements, the specific impulse of the engine was improved by 16%, and its average temperature was reduced by 19.1%.…”
mentioning
confidence: 99%